[OP.7A.02] SUSTAINED REDUCTION OF BLOOD PRESSURE WITH BARORECEPTOR ACTIVATION THERAPY: RESULTS OF SIX-YEAR OPEN FOLLOW-UP. (September 2017) - De Leeuw, P.W.; Bisognano, J.; Bakris, G.; Nadim, M.; Haller, H.; Kroon, A.
Abstract : Objective: Baroreflex Activation Therapy (BAT) is a novel technique for treating patients with resistant hypertension. Although short-term studies have demonstrated that BAT lowers blood pressure, long-term results have not yet been reported. The aim of the present study is to assess the long-term efficacy and safety of BAT. Design and method: Long-term follow-up data on blood pressure and heart rate were analyzed from all patients who have been included in one of the three BAT trials that focused on treatment-resistant hypertensive patients. These trials were the US feasibility study, the DEBut-HT trial and the pivotal trial. The first two were non-randomized, observational trials in the US and Europe respectively. In the pivotal trial patients were randomized to either immediate BAT or deferred BAT (six months after implantation). All patients who have received an implant were followed with regular visits. Results: Altogether, 383 patients were available for analysis: 143 of these had completed five years of follow-up and 48 patients had completed six years of follow-up. In the entire cohort, systolic blood pressure fell from 179+24 mmHg to 144+28 mmHg (p < 0.0001) while diastolic pressure dropped from 103+16 mmHg to 85+18 mmHg (p < 0.0001). The data further demonstrate that the greatest fall in pressure already occurs within 6 months following device implant. The blood pressure lowering effect of BAT is greater than average in patients with signs of heart failure, and less than average in patients with isolated systolic hypertension. The percentage of patients in whom systolic blood pressure at the end of follow-up had fallen below 140 mmHg was greatest in those with unilateral right-sided stimulation. In about 25% of patients it was possible to reduce the number of medications from a median of 6 to a median of 3. Temporary side effects, related to either the surgical procedure or to cardiovascular instability, do occur, but they do not require specific measures and resolve over time. Conclusions: After a follow-up of 5 years, BAT is safe and maintains its efficacy for persistent reduction of blood pressure in patients with resistant hypertension.